Prescription medications for sleep disturbances among midlife women during 2 years of follow-up: a SWAN retrospective cohort study. Issue 5 (11th May 2021) - Solomon, Daniel H; Ruppert, Kristine; Habel, Laurel A; Finkelstein, Joel S; Lian, Pam; Joffe, Hadine; Kravitz, Howard M
Abstract : Objective: To examine the effects of prescription sleep medications on patient-reported sleep disturbances. Design: Retrospective cohort. Setting: Longitudinal cohort of community-dwelling women in the USA. Participants: Racially and ethnically diverse middle-aged women who reported a sleep disturbance. Interventions: New users of prescription sleep medications propensity score matched to women not starting sleep medications. Main outcomes and measures: Self-reported sleep disturbance during the previous 2 weeks—difficulty initiating sleep, waking frequently and early morning awakening—using a 5-point Likert scale, ranging from no difficulty on any night (rating 1) to difficulty on 5 or more nights a week (rating 5). Sleep disturbances were compared at 1 year (primary outcome) and 2 years of follow-up. Results: 238 women who started sleep medications were matched with 447 non-users. Participants had a mean age of 49.5 years and approximately half were white. At baseline, sleep disturbance ratings were similar: medication users had a mean score for difficulty initiating sleep of 2.7 (95% CI 2.5 to 2.9), waking frequently 3.8 (95% CI 3.6 to 3.9) and early morning awakening 2.8 (95% CI 2.6 to 3.0); non-users ratings were 2.6 (95% CI 2.5 to 2.7), 3.7 (95% CI 3.6 to 3.9) and 2.7 (95% CI 2.6 to 2.8), respectively. After 1 year, ratings for medication users were 2.6 (95% CI 2.4 to 2.8) for initiating sleep, 3.6 (95% CI 3.4 to 3.8) for waking frequently and 2.8 (95% CI 2.6 to 3.0) for early morning awakening; for non-users, the mean ratings were 2.3 (95% CI 2.2 to 2.5), 3.5 (95% CI 3.3 to 3.6) and 2.5 (95% CI 2.3 to 2.6), respectively. None of the 1 year changes were statistically significant nor were they different between medication users and non-users. Two-year follow-up results were consistent, without statistically significant reductions in sleep disturbance in medication users compared with non-users. Conclusions: These analyses suggest that women who initiated sleep medications rated their sleep disturbances similar after 1 and 2 years. The effectiveness of long-term sleep medication use should be re-examined.